Census of India - Indien - Office of the Registrar General & Census Commissioner (2007)
[Dt.:] Der indische Zensus ist die größte Einzelquelle, die eine Bandbreite von statistischen Informationen bezüglich verschiedener Charakteristika der indischen Bevölkerung anbietet. - [Engl.:] The Indian Census is the largest single source, which offers a wide range of statistical informations concerning different characteristics of the Indian population.